Problems of banking legal relationships - Ivanov, S. U.; Іванов, С. Ю.; ORCID: http://orcid.org/0000-0003-0166-9016; Hromenko, Yu.; Хроменко, Ю.; Rodina, V.; Родина, В. (Baltic Journal of Economic Studies. - 2018. - Vol. 4, №. 5. - P. 94-99, 2018)
В сучасних умовах управління особливого значення набувають аспекти забезпечення стійкості банків та розвитку банківської системи України. Мета дослідження - визначити сутність банківських правовідносин в Україні на основі існуючих наукових підходів, чинного законодавства України та практики його застосування, а також конкретних і проблемних аспектів узгодження інтересів суб'єктів. відповідних правових відносин. Для цього розглянуто сутність і структура банківських правовідносин. У висновках статті йдеться про те, що банківське законодавство України вимагає серйозного перегляду, що стосується узгодження інтересів суб'єктів банківських правовідносин. Ключове завдання - усунути непотрібні і застарілі нормативно-правові акти, які можуть викликати юридичну плутанину або накласти надмірний тягар на суб'єкти банківських правовідносин. При розробці сучасної нормативно-правової бази для взаємодії суб'єктів банківських відносин відбувається нове швидке поширення ризиків кібер-ризиків і фінансових злочинів, що суттєво впливає на стан банківської системи і не відбивається в чинному банківському законодавстві України. Банки як основні суб'єкти банківських відносин повинні брати на себе ризики і фінансову відповідальність. Це сприятиме стабілізації банківської системи України та економічному розвитку національної економіки.

In modern conditions of management, the aspects of ensuring the stability of banks and the development of the banking system of Ukraine are of particular importance. During 2014-2017 in our country, 88 banks were recognized as insolvent, almost all of them – commercial. This tendency is disappointing. Most scholars assert that the turnaround of the banking system is possible only through the improvement of deposit, credit, and settlement operations. This statement is undoubtedly true, but these scholars forget about the importance of regulating the legal relationships that arise in the banking sector and establishing the interaction between the entities of such legal relationships. The purpose of the research is to determine the essence of banking legal relationships in Ukraine based on the existing scientifc approaches, the current legislation of Ukraine and the practice of its implementation, as well as the specifc and problematic aspects of harmonizing the interests of the entities of the relevant legal relations. For this purpose, the essence and structure of banking legal relationships are considered. It is determined that the main structural elements of these legal relationships are: 1) objects, 2) the content of banking legal relationships, 3) the basis of banking legal relationships – legal norms and legal facts, 4) entities (participants) – the direct participants in banking relationships, the bearers of mutual rights and obligations. The conclusions of the article state that Ukrainian banking legislation requires a serious revision concerning the coordination of the interests of the entities of banking legal relationships. The key task is to eliminate unnecessary and outdated normative and legal acts that could cause legal confusion or impose excessive burdens on entities of banking legal relationships. In developing the modern regulatory framework for the interaction of entities of banking relationships, a new rapid spread of cyber-risks, compliance risks and fnancial crime risks, which signifcantly aﬀects the state of the banking system and is not reﬂected in the current banking legislation of Ukraine, should be taken into consideration. Banks as the main entities of banking relationships should assume risks and fnancial responsibility. It will contribute to the stabilization of the banking system of Ukraine and the economic development of the national economy.

В современных условиях управления особое значение приобретают аспекты обеспечения устойчивости банков и развития банковской системы Украины. Цель исследования - определить сущность банковских правоотношений в Украине на основе существующих научных подходов, действующего законодательства Украины и практики его применения, а также конкретных и проблемных аспектов согласования интересов субъектов. соответствующих правовых отношений. Для этого рассмотрены сущность и структура банковских правоотношений. В выводах статьи говорится, что банковское законодательство Украины требует серьезного пересмотра, касающегося согласования интересов субъектов банковских правоотношений. Ключевая задача - устранить ненужные и устаревшие нормативно-правовые акты, которые могут вызвать юридическую путаницу или наложить чрезмерное бремя на субъекты банковских правоотношений. При разработке современной нормативно-правовой базы для взаимодействия субъектов банковских отношений происходит новое быстрое распространение рисков кибер-рисков и финансовых преступлений, что существенно влияет на состояние банковской системы и не отражается в действующем банковском законодательстве Украины. Банки как основные субъекты банковских отношений должны брать на себя риски и финансовую ответственность. Это будет способствовать стабилизации банковской системы Украины и экономическому развитию национальной экономики.
Ivanov, S. Problems of banking legal relationships / Stanislav Ivanov, Yuliia Hromenko, Valeriia Rodina // Baltic Journal of Economic Studies. - 2018. - Vol. 4, №. 5. - P. 94-99. - DOI: htps://doi.org/10.30525/2256-0742/2018-4-5-94-99.
Ivanov, S., Yu. Hromenko, and V. Rodina. "Problems of banking legal relationships." Baltic Journal of Economic Studies 4.5 (2018): 94-99. Print.
Keywords: Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; Наукові публікації. Scientific publications. Научные публикации; publikatsii u zarubizhnomu vydanni; publikatsii u WoS; банк; банківська діяльність; bank; banking service; entity; legal relationships; banking system; interests; банківська служба; суб’єкт господарювання; правовідносини; банківська система; інтереси; юридические лица; правоотношения; банковская система; интересы